2019
DOI: 10.1007/978-3-030-19955-5_2
|View full text |Cite
|
Sign up to set email alerts
|

The Non-hardness of Approximating Circuit Size

Abstract: The Minimum Circuit Size Problem (MCSP) has been the focus of intense study recently; MCSP is hard for SZK under rather powerful reductions [4], and is provably not hard under "local" reductions computable in TIME(n 0.49 ) [26]. The question of whether MCSP is NP-hard (or indeed, hard even for small subclasses of P) under some of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Thus one avenue for proving a hardness result for MCSP had seemed to be to improve the hardness result for MKTP, so that it worked for a much larger "gap". This avenue was subsequently blocked, when it was shown that PARITY is not AC 0 -reducible to GapMCSP (or to GapMKTP) for a moderate-sized "gap" [12]. Thus, although it is still open whether MCSP is NP-complete under ≤ AC 0 m reductions, we now know that GapMCSP is not NP-complete under this notion of reducibility.…”
Section: Negative Hardness Resultsmentioning
confidence: 99%
“…Thus one avenue for proving a hardness result for MCSP had seemed to be to improve the hardness result for MKTP, so that it worked for a much larger "gap". This avenue was subsequently blocked, when it was shown that PARITY is not AC 0 -reducible to GapMCSP (or to GapMKTP) for a moderate-sized "gap" [12]. Thus, although it is still open whether MCSP is NP-complete under ≤ AC 0 m reductions, we now know that GapMCSP is not NP-complete under this notion of reducibility.…”
Section: Negative Hardness Resultsmentioning
confidence: 99%
“…Thus one avenue for proving a hardness result for MCSP had seemed to be to improve the hardness result of [6], so that it worked for a much larger "gap". This avenue was subsequently blocked, when it was shown that PARITY is not AC 0 -reducible to GapMCSP (or to GapMKTP) for a moderate-sized "gap" [8]. Thus, although it is still open whether MCSP is NP-complete under ≤ AC 0 m reductions, we now know that GapMCSP is not NP-complete under this notion of reducibility.…”
Section: Completeness Hardness Reducibilitymentioning
confidence: 99%